Involvement of the endoplasmic reticulum in the assembly and envelopment of African swine fever virus. - Cobbold, C (1996)
African swine fever (ASF) virus is a large enveloped DNA virus assembled in the cytoplasm of cells. In this study, the membrane compartments involved in the envelopment of ASF virus were investigated. A monoclonal antibody recognizing p73, the major structural protein of ASF virus, was generated to analyze the binding of p73 to membranes during the assembly of the virus. Approximately 50% of the intracellular pool of p73 associated with membranes as a peripheral membrane protein. Binding was rapid and complete within 15 min of synthesis. Subcellular membrane fractionation showed that newly synthesized p73 molecules cosedimented with endoplasmic reticulum (ER) membranes and remained associated with the ER during a 2-h chase. A similar distribution on gradients was recorded for p17, a structural membrane protein of ASF virus. The results suggested that the ER was involved in the assembly of ASF virus. A protease protection assay demonstrated a time-dependent envelopment of the membrane bound, but not cytosolic, pool of p73. Envelopment of p73 took place 1 h after binding to membranes and was completed 1 h before the first detection of p73 in virions secreted from cells. Envelopment was unaffected by brefeldin A and monensin, drugs that block membrane transport between the ER and Golgi. Taken together the results provide evidence for the binding of ASF virus structural proteins to a specific membrane compartment and implicate a role for the ER in the assembly and envelopment of ASF virus.